Antibacterial Activity Testing of Methanol Extract of Yellow Rope Barb (Anamirta cocculus) - Wa Ode Nurwahida; A.M. Muslihin; Lukman Hardia (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia has abundant natural wealth. One of the endemic plants of Papua which is often used in traditional medicine is yellow rope (A. cocculus). This study aims to determine the antibacterial activity of methanol extract of yellow rope bark (A. cocculus) against P. acnes, S. aureus, and E. coli bacteria using an experimental microbiological approach in the laboratory, and the experiment model may also serve as a contextual laboratory-based learning resource in microbiology education. The antibacterial activity test was carried out using the disc diffusion method which was made in 3 concentrations, namely 5%, 10% and 15%. The results of measuring the diameter of the inhibition zone showed that each concentration was able to inhibit the growth of P. acnes bacteria with an average diameter of 2,816 mm (Weak), 6,733 mm (Medium), 9,333 mm (Medium), and control (+) clindamycin 2 μg 14,483 mm (Strong). S. aureus bacteria with an average diameter of 3.133 mm (Weak), 6.35 mm (Medium), 8.235 mm (Medium) and control (+) clindamycin 2 μg 20.97 mm (Very strong). E. coli bacteria showed an average diameter of 3.875 mm (Weak), 6.175 mm (Medium), 8.566 mm (Medium) and control (+) ciprofloxacin 5 μg 20.783 mm (very strong). This research shows that the methanol extract of yellow stem bark (A. cocculus) has antibacterial activity.